2021
DOI: 10.1016/j.cdtm.2021.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparative outcomes of endoscopic ultrasound‐guided lumen‐apposing mental stents drainage for pancreatic pseudocysts and walled‐off necrosis: Case series and meta‐analysis

Abstract: Background Endoscopic ultrasound (EUS)-guided transmural drainage for pancreatic fluid collections (PFCs) has become the first-line treatment with quicker recovery and more minor injury compared with surgery and percutaneous drainage. The efficacy of stents implantation and drainage for different PFCs remains controversial, especially lumen-apposing metal stents (LAMS). This study aimed to compare the efficacy and safety of LAMS drainage for pancreatic pseudocysts (PPC) and walled-off necrosis (WO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…Another case series and meta-analysis by Li et al. [ 40 ] also reported that for PFC, LAMS showed preferable clinical success and AEs. A meta-analysis of eleven studies comparing the data of 688 patients with PFC through the LAMS and the DPS indicated that the LAMS showed better efficacy in managing PFC [ 41 ].…”
Section: Discussionmentioning
confidence: 98%
“…Another case series and meta-analysis by Li et al. [ 40 ] also reported that for PFC, LAMS showed preferable clinical success and AEs. A meta-analysis of eleven studies comparing the data of 688 patients with PFC through the LAMS and the DPS indicated that the LAMS showed better efficacy in managing PFC [ 41 ].…”
Section: Discussionmentioning
confidence: 98%
“…Xu et al [ 91 ] reported that EUS outperformed CT in accurately categorizing symptomatic peripancreatic fluid collections and emerged as a preferred imaging modality for detecting solid necrotic debris. EUS-guided lumen-apposing metal stents for pancreatic fluid collections were feasible and effective with preferable technical and clinical success rates[ 92 ].…”
Section: Imaging Technologymentioning
confidence: 99%
“…By contrast, LAMS are characterized by large-bore caliber sizes with extended patency and offer unimpeded access to the cavity for direct necrosectomies. However, stent migration and bleeding have been described as relevant adverse events [10,11].…”
Section: Introductionmentioning
confidence: 99%